A blind detection method for spatial modulation in MIMO communications. Issue 4 (24th December 2020) - Khanzadeh, Roya; Naeiny, Mahmoud Ferdosizade
Abstract: Spatial modulation (SM) is one of the probable candidates to be utilised in the fifth generation of wireless networks due to its power and spectral efficiencies. Since only one active transmit antenna exists in spatial modulation, inter‐channel interferences are avoided and the number of radio frequency (RF) chains is reduced. However, channel estimation is a major challenge in spatial modulation communication systems. In this study, a novel blind signal and channel estimation method for spatial modulation‐based multi‐input multi‐output communications, based on the well‐known Expectation‐Maximisation algorithm, is presented. This blind detector requires only a few pilot symbols at the beginning of the transmission to resolve the inherent phase and permutation ambiguities. Simulation results demonstrate that the proposed detector performs very similar to the optimum detector with full channel state information and outperforms existing blind detectors.